2020
DOI: 10.1002/gdj3.108
|View full text |Cite
|
Sign up to set email alerts
|

Ukrainian early (pre‐1850) historical weather observations

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…Slivinski et al (2019a) investigated how well the 20CRv3 system represents the 1915 Galveston Hurricane, and found that 20CRv3 has the strongest intensity (i.e., lowest central pressure) of the four historical reanalyses considered there: 20CRv2c, 20CRv3, ERA-20C, and CERA-20C. Here, we investigate an extratropical winter storm that impacted North America in the nineteenth century and has been the focus of several previous studies (Kocin 1983(Kocin , 1988Michaelis and Lackmann 2013), but 20CRv3 could be used to study a variety of weather extremes back to 1806 (e.g., the 1816 year without a summer; Brugnara et al 2015;Skrynyk et al 2021).…”
Section: Case Study: the Great Blizzard Of 1888mentioning
confidence: 99%
“…Slivinski et al (2019a) investigated how well the 20CRv3 system represents the 1915 Galveston Hurricane, and found that 20CRv3 has the strongest intensity (i.e., lowest central pressure) of the four historical reanalyses considered there: 20CRv2c, 20CRv3, ERA-20C, and CERA-20C. Here, we investigate an extratropical winter storm that impacted North America in the nineteenth century and has been the focus of several previous studies (Kocin 1983(Kocin , 1988Michaelis and Lackmann 2013), but 20CRv3 could be used to study a variety of weather extremes back to 1806 (e.g., the 1816 year without a summer; Brugnara et al 2015;Skrynyk et al 2021).…”
Section: Case Study: the Great Blizzard Of 1888mentioning
confidence: 99%
“…Nonetheless, in recent years, there has been a renewed interest in tracking down and digitizing station history metadata for many countries and individual stations in the recognition that this can help identify genuine non-climatic breakpoints, e.g., [46][47][48][49][50][51][52][53][54][55][56][57][58]. Unfortunately, the levels of detail and comprehensiveness of the station history metadata currently available vary substantially between countries.…”
Section: A Case Study Of the Ukrainian Resultsmentioning
confidence: 99%
“…Therefore, if we are interested in using these records to study regional, hemispheric or global temperature trends, it is important to accurately account for these biases. Indeed, many of us are actively engaged in developing and/or improving the reliability of the available temperature records for Europe [18,19,35,[44][45][46]49,[56][57][58][59][69][70][71][75][76][77][78][79] and elsewhere [18,19,38,39] through various homogenization techniques and/or the collection of more data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations